Integration neuer Technologien der Bitumenkalthandhabung in die Versorgungskette - Wunder, Marius (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2015)
According to new technological abilities, bitumen is today again transported and stored under normal temperatures to be remelted afterwards. The detailed determined costs of the handling technologies are integrated into a linear optimization model for combined technology-, location and capacity-planning. The model is used to optimize the production network of a reference company and shows, that it is possible to use the packing- and remelting-techniques for bitumen to reduce the production costs